2010
DOI: 10.3109/02770901003759402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rhinitis on Asthma Control in Children: Association With FeNO

Abstract: Our study confirms the strong relationship between upper airways and poor asthma control in the asthmatic child. Symptoms of rhinitis may be partly responsible for the increased fractional exhaled nitric oxide (FeNO) level, independently of the control of asthma. Evaluation of rhinitis should be included to improve assessment of asthma control in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
3
12
0
2
Order By: Relevance
“…However, studies have shown that asthma is still not fully controlled in many patients [33, 34]. Despite environmental and allergic factors and poor adherence to treatment, rhinitis has been recognized as a cause of poor asthma control, and the development of rhinitis may be an indicator of persistent asthma [4, 35]. To date, there are few objective tools for evaluating rhinitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies have shown that asthma is still not fully controlled in many patients [33, 34]. Despite environmental and allergic factors and poor adherence to treatment, rhinitis has been recognized as a cause of poor asthma control, and the development of rhinitis may be an indicator of persistent asthma [4, 35]. To date, there are few objective tools for evaluating rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…One study found the comorbidity of rhinitis and asthma to be as high as 100% [2]. Local allergen exposure in the nose of patients with allergic rhinitis can quickly lead to asthma or significant allergic inflammation in the lung [3], with an elevation of fractional exhaled nitric oxide (FeNO) [4]. It is important for pediatricians to understand the relationship between these two disorders that all children with rhinitis are evaluated for lower airway disease, and all patients with asthma are screened for upper airway conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Rhinitis was more frequent when control of asthma was worse. 37 Both retrospective and prospective claims data show that treating AR reduces asthma-related hospitalizations and emergency room visits by about half.…”
Section: Ar Control Impacts Asthma Controlmentioning
confidence: 99%
“…Measuring fractional exhaled nitric oxide (FeNO) is a validated inflammatory marker in the diagnosis and management of patients with asthma, atopy, and allergic rhinitis (AR). [1][2][3] It is a useful, reproducible, noninvasive tool and easy to perform in a short time. However, interpretation is usually difficult because of interfering factors such as height, age, gender, lung function, smoking, and respiratory tract infections.…”
Section: T He Magnitude Of Nitric Oxide (No) Concentration In Exhaledmentioning
confidence: 99%